Analisis Laporan Keuangan Untuk Menilai Kinerja Keuangan Pt. Unilever Indonesia Tbk - Nieko Siregar; Ratih Kusumastuti (Pusat Riset dan Inovasi Nasional, 2023)
. PT. Unilever Indonesia Tbk's financial performance was evaluated using financial statement analysis. The purpose of this study is to analyze and determine how PT. Unilever Indonesia Tbk. The issue under investigation is the state of PT. Unilever Indonesia Tbk.'s financial performance from 2020 to 2021. Financial ratio analysis, which employs the time series analysis method for businesses, is the analytical instrument employed. It comprises liquidity ratios, solvency ratios, activity ratios, and profitability ratios. This study uses calculations on quantitative data from year-end closing financial statements (secondary data) from 2020 to 2021 in a qualitative quantitative descriptive approach.